2016
DOI: 10.1016/j.jclepro.2015.09.078
|View full text |Cite
|
Sign up to set email alerts
|

Consumer trust in different food provisioning schemes: evidence from Beijing, China

Abstract: a b s t r a c tConsuming safe and sustainable food requires trust. Consumer trust in food can be established in different ways, including through personal relationships or various institutional arrangements established by government, private companies and/or civil-society organisations. The recent increase in foodsafety incidents and sustainability concerns in China suggests a dwindling trust in the current government-dominated food governance arrangement. This paper investigates whether emerging alternative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 45 publications
6
71
0
Order By: Relevance
“…Fake news reports that have required clarification include fishermen using contraceptives to expedite growth of swamp eel (a species of fish in China), and McDonald's using genetically modified six-wing chickens for their products (CFDA, 2017). More importantly, studies found that most consumers regard the government as the most reliable source of information, even though they believed official information was underreported (Li et al 2012;Liu, Pieniak & Verbeke, 2013;Zhang, Xu, Oosterveer & Mol, 2016).…”
Section: Transparency Of Governancementioning
confidence: 99%
See 1 more Smart Citation
“…Fake news reports that have required clarification include fishermen using contraceptives to expedite growth of swamp eel (a species of fish in China), and McDonald's using genetically modified six-wing chickens for their products (CFDA, 2017). More importantly, studies found that most consumers regard the government as the most reliable source of information, even though they believed official information was underreported (Li et al 2012;Liu, Pieniak & Verbeke, 2013;Zhang, Xu, Oosterveer & Mol, 2016).…”
Section: Transparency Of Governancementioning
confidence: 99%
“…Governance is therefore more than simply describing the role of the government in food policy. Disclosure of information is an essential part of food safety governance (FAO & WHO, 2003) and while the government is often the most trusted source, the majority of Chinese consumers still receive information on food safety incidents from the media (Jin & Han, 2014;Peng, Li, Xia, Qi & Li, 2015;Zhang, Xu, Oosterveer & Mol, 2016). The sharp increase in Chinese media exposure of food safety incidents (Liu & Ma, 2016) shows the media's role in food safety governance.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers' trust in food information communicated by public organisations is greater than by private associations (Nocella et al 2014). For example, Zhang et al (2016) found that government was the most trustworthy source of information concerning food safety, compared to private certification schemes, e.g. the Safe Quality Food (SQF) Program, a civil-society organisation.…”
Section: Consumer Trustmentioning
confidence: 99%
“…This can be illustrated in the case where trust is undermined and consumers are confronted with crises and uncertainty. During the melamine-scandal, the poisoned baby-milk powder in China some years ago, consumers were forced to reconsider what food to buy and where to buy it (Zhang et al, 2016). Their main consideration in shopping for food was the health of their children and they searched for ways to regain trust in the food supply system.…”
Section: Consumers and Food Consumption Practicesmentioning
confidence: 99%